Ritmo e durata fra Husserl e Bachelard - Serra, Carlo (Bollettino Filosofico, 2018)
Inside phenomenological research, the concepts of present time and instant are characterized by a troubled dialectic: for Husserl the present flows, widening both towards the past and the future, like the Heraclitean bowstring which stretches between two dimensions. Gaston Bachelard, on the contrary, is the thinker of discreteness, in which the temporal continuum is linked to the reciprocal differentiation of instants in duration. Therefore, the conceptions of time of these philosophers seem to be opposed to one another. However, within these two modalities of scansion, we meet a common thread, which underlies both interpretations and allows for their convergence on the perceptual content. We will focus, on the one hand, on the process through which the position acquires its shape within Bachelard’s La dialectique de la durée (1936), and, on the other hand, on Husserl’s treatment of the way in which one aspect of the thing emerges above the others in his writings on attention (1904-1905).